Else Feldmann: Schreiben vom Rand: Journalistin und Schriftstellerin im Wien der Zwischenkriegszeit - Debazi, Elisabeth (2021)
The work deals with the life and work of the Jewish journalist and writer Else Feldmann, who herslf coming from a poor background, describes the life of the marginalized in Vienna during the interwar period. She has written numerous reports for newspapers and magazines as well as a play for the theater and three novels.